Assessing Competitiveness After Conflict The Case of the Central African Republic - Lewis, Mark (International Monetary Fund, 2006)
This paper assesses competitiveness in the case of the Central African Republic, a postconflict country. The paper presents several conventional techniques for assessing competitiveness, namely the real exchange rate and recent trade performance. Several other measures are considered, in particular transport costs and governance measures, which may be more effective in capturing the obstacles to competitiveness posed by the poor security environment and weak institutions common to many post-conflict situations. The real exchange measure and trade measures suggest some mild erosion of competitiveness in recent years, while the other measures indicate that the competitiveness challenges faced by the Central African Republic are much deeper